Cytoreductive nephrectomy in patients with metastatic renal cell carcinoma and venous thrombus—trends and effect on overall survival - Lwin, Aye A.; Pollock, Grant R.; Chipollini, Juan (Annals of Translational Medicine; Vol 7, Supplement 6 (September 20, 2019): Annals of Translational Medicine, 2019)
Cytoreductive nephrectomy (CN) combined with cytokine therapy was once the standard of care for metastatic renal cell carcinoma (mRCC) (1,2). In the past decade, there have been a myriad of novel therapies in metastatic renal cell carcinoma treatments including targeted therapies such as tyrosine kinase inhibitors (TKIs), mammalian target or rapamycin (mTOR) inhibitors, VEGF inhibitors, and PD-1 inhibitors.